Neuroligin-1 is required for normal expression of LTP and associative fear memory in the amygdala of adult animals - Kim, Juhyun; Jung, Sang-Yong; Lee, Yeon Kyung; Park, Sangki; Choi, June-Seek; Lee, C. Justin; Kim, Hye-Sun; Choi, Yun-Beom; Scheiffele, Peter; Bailey, Craig H.; Kandel, Eric R.; Kim, Joung-Hun (NATL ACAD SCIENCES, 2008)
Neuroligin-1 is a potent trigger for the de novo formation of synaptic connections, and it has recently been suggested that it is required for the maturation of functionally competent excitatory synapses. Despite evidence for the role of neuroligin-1 in specifying excitatory synapses, the underlying molecular mechanisms and physiological consequences that neuroligin-1 may have at mature synapses of normal adult animals remain unknown. By silencing endogenous neuroligin-1 acutely in the amygdala of live behaving animals, we have found that neuroligin-1 is required for the storage of associative fear memory. Subsequent cellular physiological studies showed that suppression of neuroligin-1 reduces NMDA receptor-mediated currents and prevents the expression of long-term potentiation without affecting basal synaptic connectivity at the thalamo-amygdala pathway. These results indicate that persistent expression of neuroligin-1 is required for the maintenance of NMDAR-mediated synaptic transmission, which enables normal development of synaptic plasticity and long-term memory in the amygdala of adult animals.
Keywords: LONG-TERM POTENTIATION; SYNAPTIC-TRANSMISSION; INHIBITORY SYNAPSES; ADHESION MOLECULE; LATERAL AMYGDALA; AUTISM; PLASTICITY; MODULATION; MUTATION; PATHWAY